2017
DOI: 10.1039/c7ra03640j
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicle release and micellar attack as the alternative mechanisms involved in the red-blood-cell-membrane solubilization induced by arginine-based surfactants

Abstract: Two novel arginine-based surfactants, Bz-Arg-NHC 10 and Bz-Arg-NHC 12 , were characterized with respect to surface properties and their interaction with human red-blood-cell (HRBC) membranes. The values for critical micellar concentration (CMC), the maximum surfactant adsorption at the air-liquid interface, and the area per molecule indicated better surface properties for Bz-Arg-NHC 12 . The observation of cylindrical worm-like aggregates of Bz-Arg-NHC n via atomic-force microscopy supported the predictions ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Despite the weaker antibacterial activity of INH@smMNP, this paper prefers to reduce the potential unintended effects of MNPs by applying surface modification. Besides, the particular amphiphilic structure of lipoamino acid could partially mimic the natural structure of the cell membrane (29,30). Several studies have taken advantage of this characteristic to increase drug efficacy, especially antibiotics (11).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the weaker antibacterial activity of INH@smMNP, this paper prefers to reduce the potential unintended effects of MNPs by applying surface modification. Besides, the particular amphiphilic structure of lipoamino acid could partially mimic the natural structure of the cell membrane (29,30). Several studies have taken advantage of this characteristic to increase drug efficacy, especially antibiotics (11).…”
Section: Discussionmentioning
confidence: 99%
“…As we previously demonstrated, HRBC irreversibly lose surface area and volume due to exovesiculation induced byBz-Arg-NHC12 [20]. When incorporated into the membrane, this kind of arginine-based compound-having a bulky head with a benzoyl group attached to itare unable to equilibrate rapidly between the outer-and the inner-membrane monolayers.…”
Section: Solubilization Of Phospholipids By Bz-arg-nhc12mentioning
confidence: 84%
“…The HC50/CMC ratio was also calculated, since it gives a hint about the surfactant's form responsible for the hemolytic effect. Considering the CMC value calculated for Bz-Arg-NHC12 was 0.085 mM [20], HC50/CMC ratios for HRBC and SRBC were 16.6 and 18.7 respectively.…”
Section: Effect Of Bz-arg-nhc12 On Red Blood Cellsmentioning
confidence: 96%
“…This action is due to the fact that lipids, surfactants and transferrin act synergistically, promoting the escape of DNA complexes from endosomes, thus improving transfection compared to systems without surfactants. The mechanism of arginine surfactant action on the membranes of human red blood cells was discussed in one study [69], which reported that the destruction of erythrocyte membranes proceeded in two ways. At low surfactant concentrations, the incorporation of surfactant monomers into the erythrocyte membrane with subsequent detachment of microvesicles was responsible for hemolysis.…”
Section: Amino Acid Surfactantsmentioning
confidence: 99%